(untitled) (IITM JOURNAL OF BUSINESS STUDIES (JBS), 2022)
Covid-19 pandemic has changed the Indian TV and video market. OTT platforms saw a sudden increase in popularity and subsequent increase in subscription. However, the recent announcement of price cut in Netflix’s subscription packages once again brings to the foray the effect of pricing on purchase behavior. Following Netflix, other OTT players also announced similar subscription offers. Present research aims to study of the effect of odd pricing (or 9-ending pricing) and discount pricing on the purchase intention. It is intended to answer questions on the extent to which pricing policies affect purchase of media products and how customers perceive the value-based pricing concept of OTT players. Research findings indicate that there is a positive relationship between pricing policies and purchase intention of OTT subscription packages. The results also show that the pricing strategies affect the purchase of media products and perceived price fairness has a positive impact on purchase intention.